Bone changes associated to disc disease - Jose Angel Martínez López (Medisan, 2016)
The magnetic resonance has provided new opportunities of disk-vertebral pathological findings.  It is not considered important in asymptomatic patients, but it is a significant emergence in the vertebral degeneration of discal cause that, according to the intensity of the signs, it was classified by Modic as sequences T1 and T2. Although controversy exists as for the disc disease, the resonance is the only available test to correlate the imagenologic findings with the symptoms of the patient affected.